The effect of e-learning media application using problem based learning models to activities and results of student learning in salt hydrolysis subject - Nisa Humairah; Marini Damanik; Eddyanto Eddyanto (Jurnal Pendidikan Kimia (JPKim), 2018)
This study purpose to determine the improvement of chemical learning outcomes and student learning activities that used e-learning media with problem based learning models on the subject of salt hydrolysis. The design was used One Group Pretest and Postest. The instrument used two domains, namely cognitive and affective. Hypothesis testing is carried out using the two-part of t-test. The hypothesis’s test of student learning outcomes obtained tcount = 29.5 while ttable = 2.03 for α = 0.05 and db = 34. Thus tcount> ttable then the hypothesis of Ha is accepted. It concluded that there is an improvement in students' chemistry learning outcomes on salt hydrolysis subject that used e-learning media with problem based learning models. Not only the percentage increased in learning outcomes of 68.4%, but also the percentage of student learning activities of 84% which means very active.Keywords:e-learning; learning activities; learning outcomes; problem based learning